Tinjauan Hukum Islam Terhadap Praktik Couple Conseling dalam Mengatasi Kekerasan dalam Rumah Tangga di Rifka Annisa Women Crisis Center (WCC) Tahun 2012 - Ulinuha Wijayanti; Malik Ibrahim (UIN Sunan Kalijaga Yogyakarta, 2013)
Marriage is bond born inwardness between a man with a woman as man andwife, with purpose form family that eternal and happy based on by Godhead ThatMaha Esa. Although marriage own purpose that is noble, however marriage can onlyrocky until setting by the ears, even can pointed in broken by her marriage. Howeverneed to be known that at basic it who became reason divorce is happened by him syiqaq(dispute that already implacable) between husband with wife that partly due to KDRT,until needed by third-party as mediator. So Rifka Annisa as Non-governmentalOrganization that concerns with Domestic Violence (KDRT) that Isteri as the victimprovide some solution in overcome KDRT, one of the solution namely CoupleConseling. Formulation internal problem this writing is: How Couple Conselingpractice in Rifka Annisa in overcome domestic violence? And whether CoupleConseling practice that applied in Rifka Annisa in trying peace collateral with Hakamconcept in Islamic law?This writing is field research that descriptive analytical, method used to collectdata use interviewing technique as the main technique and documentation as techniquesupporter, which then analyzed by using qualitative method analysis, next wereanalyzed with deductive method. Based on by working through inferential as follows,that first, Couple Conseling practice in Rifka Annisa in overcome domestic violenceconducted with Man's Program program, that in the activity be done in three stage.That second, Rifka Annisa practice in make counseling to client as mediator ormediator have accordance jury concept in Islamic law, because acquiescent political andcivil life scholars that mediator can sent good on part husband or wife or someone elsethat not from wife husband couple family. In this case Rifka Annisa is one of LSMthat appropriate to be appointed as mediator.